104k views
2 votes
What is the product? (x square root 7 - 3 square root 8) (x square root 7 - 3 square root 8)

2 Answers

2 votes

Answer:


7x^2-12x√(14)+72

Explanation:

First we write the product

(x square root 7 - 3 square root 8) (x square root 7 - 3 square root 8)

This is:


(x√(7)-3√(8))(x√(7)-3√(8))

Now apply the distributive property as shown below.


(x√(7)-3√(8))(x√(7)-3√(8))=x√(7)*x√(7) -3√(8)*x√(7)-3√(8)*x√(7) +3√(8)*3√(8)


(x√(7)-3√(8))(x√(7)-3√(8))=(x√(7))^2 -6x√(7)*√(8)+9*(√(8))^2\\\\\\(x√(7)-3√(8))(x√(7)-3√(8))=7x^2 -12x√(7*2)+9*8\\\\(x√(7)-3√(8))(x√(7)-3√(8))=7x^2-12x√(14)+72

User Patrick Hurst
by
6.4k points
1 vote

Answer:

The product is
7x^2-12x√(14)+72

Explanation:

We need to find product of:


(x√(7)-3√(8) )(x√(7)-3√(8))

We need to multiply these terms


=x√(7)(x√(7)-3√(8))-3√(8)(x√(7)-3√(8))\\=x^2(√(7))^2-3x(√(7)*√(8))-3x(√(8)*√(7))+9(√(8))^2\\=x^2(7)-6x(√(7)*√(8))+9(8)\\=7x^2-6x√(56)+72 \\√(56)=2√(14)\\=7x^2-6x*2√(14)+72\\=7x^2-12x√(14)+72

So, the product is
7x^2-12x√(14)+72

User RaviH
by
6.4k points